AIRSHIPS ARE BACK - Макарчук, Таїсія; Чурсанова, Марина; Дрозденко, Олександра (SWorldJournal, 2026)
This paper presents a review of modern trends in the development of airships and their role in solving the current problems of humankind related to ecology and logistics. Unlike traditional aviation, airships enable transportation with significantly lower